Pengaruh Kualitas Informasi, Kualitas Layanan dan Persepsi Manfaat terhadap Kepuasan Pengguna Aplikasi Dana pada Mahasiswa Fakultas Ekonomi Universitas Negeri Medan - Panjaitan, Eurica Imannuela Elfri br.; Darma, Jufri; Kholis, Azizul; Siregar, Tapi Rumondanag Sari; Hidayat, Taufik (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The DANA application is an important non-cash payment platform for users, especially to assess quality and increase their satisfaction. This research aims to analyze the influence of information quality, service quality and perceived benefits on DANA application user satisfaction among students at the Faculty of Economics, Medan State University. The research population consisted of students who used the DANA application, with a sample of 100 respondents taken using convenience sampling techniques. Data were analyzed using the Partial Least Square (PLS) method via SmartPLS software, which includes the PLS Algorithm test, Bootstrapping, and hypothesis testing with a p-value < 0.05. The analysis results show that the average variance is above 0.5 and the outer loading indicator is greater than 0.7. The first hypothesis, which states that information quality influences DANA application user satisfaction, is accepted with a p-value of 0.000 < 0.05. The second hypothesis, which states that service quality influences DANA application user satisfaction, was also accepted with a p-value of 0.017 < 0.05. The third hypothesis, which states that perceived usefulness influences DANA application user satisfaction, is accepted with a p-value of 0.003 < 0.05.